Transformational Leadership and Job Satisfaction: A Study of Creative Industries in Asia. - Marliana, Thika; Yanuar , Ignatius Erik Sapta; Sova, Maya; Rosa, Tina; Tamba, Mariati; Boonsawad, Panicha; Kurniawati, Indah (Darussalam: Journal of Psychology and Educational, 2024)
This research explores the relationship between transformational leadership and job satisfaction in the creative industry in Asia, which is known for its unique dynamics and challenges. In this context, transformational leadership, characterized by the leader's ability to inspire, motivate, and empower employees, is viewed as a key factor in enhancing job satisfaction. This research aims to understand how elements of transformational leadership, such as a clear vision, effective communication, and attention to individual needs, can contribute to employees' feelings of satisfaction and engagement in their work. The research methods used include surveys and in-depth interviews with employees and leaders from various creative sectors, including art, media, and design. The collected data were analyzed to identify significant patterns and relationships between leadership practices and job satisfaction levels. The research results show that leaders who implement transformational leadership strategies not only succeed in creating a work environment that supports innovation and creativity but also enhance employee motivation and commitment. Most respondents reported that they felt more engaged and satisfied when working under leaders who adopted this approach. These findings provide valuable insights for organizations in designing effective leadership strategies in the creative sector, as well as highlighting the importance of paying attention to individual needs in the effort to achieve organizational goals. Thus, this research not only contributes to the academic literature on leadership and job satisfaction but also provides practical guidance for leaders and managers in enhancing job satisfaction in dynamic and creative environments. The recommendations generated from this research can help organizations in building a positive and productive work culture, thereby contributing to long-term success in the creative industry.